Optical properties of aerosol particles in the atmospheric boundary layer in regions with and without sea ice - Koga, Seizi (Polar Science, 2021)
The optical properties of aerosol particles must be clearly understood to reduce uncertainty in the prediction of the global climate change. Simultaneous measurements of scattering and absorption coefficients of aerosol particles were conducted in the atmospheric boundary layer over the western North Pacific and the Southern Ocean. For the scattering coefficient, total scattering and backscattering coefficients were measured at three different wavelengths. Over the western North Pacific, significant differences in the Ångström exponent and absorption coefficient were found between polluted and pristine air masses. Over the parts of the Southern Ocean free of sea ice, the Ångström exponent and the ratio of the back-to total-scattering coefficients were uniform. However, over the sea-ice regions, the scattering coefficients were an order of magnitude lower, and the Ångström exponent an order of magnitude higher, than over the parts of the ocean free of sea ice. These differences appear to be due to the fact that the emission of aerosol precursors and sea salt particles is suppressed by sea ice. This study represents the difference in aerosol optical properties as a function of source region and sea condition. These results will contribute to improving the accuracy of estimates of the direct radiative forcing effects due to aerosol particles. journal article